Recent developments and innovative applications in computational mechanics - Mueller-Hoeppe, Dana.; Loehnert, Stefan; Reese, Stefanie; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Festschrift is dedicated to Professor Dr.-Ing. habil. Peter Wriggers on the occasion of his 60th birthday. It contains contributions from friends and collaborators as well as current and former PhD students from almost all continents. As a very diverse group of people, the authors cover a wide range of topics from fundamental research to industrial applications: contact mechanics, finite element technology, micromechanics, multiscale approaches, particle methods, isogeometric analysis, stochastic methods and further research interests. In summary, the volume presents an overview of the international state of the art in computational mechanics, both in academia and industry.
New applications of mortar methodology to extended and embedded finite element formulations -- Thermo-mechanical coupling in beam-to-beam contact -- On regularization of the convergence path for the implicit solution of contact problems -- On different variational formulations of the Nitsche method -- Challenges in computational nanoscale contact mechanics -- On the four-node quadrilateral element -- Stability of mixed finite element formulations a new approach -- A finite element formulation based on the theory of a Cosserat point modification of the torsional modes -- A brick element for finite deformations with inhomogeneous mode enhancement -- Automatic differentiation based formulation of computational models -- Nonlinear finite element shell formulation accounting for large strain material models -- Hybrid and mixed variational principles for the geometrically exact analysis of shells -- A shell theory with scale effects, higher order gradients, and meshfree.
Electronic reproduction.
Keywords: Mechanics, Applied; Electronic books